Levels of non-essential (Cd, Pb and Hg) elements in muscle tissues of Anguilla bicolor bicolor, McClelland 1844 from Kedah and Anguilla bengalensis bengalensis, Gray 1831 from Perak and human consumption risks - Noraifaa Abdullah Sani,; Noor Azhar Mohamed Shazili,; Ong, Meng Chuan; Takaomi Arai, (Penerbit Universiti Kebangsaan Malaysia, 2019)
A study on heavy metals accumulation and human health risk assessment in the consumption of two tropical freshwater eel species (Anguilla bengalensis bengalensis) from the Sungai Perak at Kuala Kangsar, Perak and (Anguilla bicolor bicolor) from the Air Hitam irrigation canal, Kampung Kuala Sanglang, Kedah was carried out. Specimens were examined and analyzed for Pb and Cd concentrations using ICP-MS while the total Hg concentration was measured using a direct mercury analyzer (MA-3000). The range for the total concentrations (μg/g wet wt.) in Anguilla bicolor bicolor were 0.01-0.4 (Cd), 0.03-0.77 (Pb) and 0.36-0.94 (Hg) while for Anguilla bengalensis bengalensis, they were 0.76-1.23 (Cd), 0.01-0.10 (Pb) and 0.27-1.5 (Hg). Anguilla bengalensis bengalensis (Sungai Perak) showed a significant strong relationship between Hg/Pb (r = .771, P < 0.05) and Anguilla bicolor bicolor (Air Hitam irrigation canal) with Cd/Pb (r = -.895, P < 0.05) in muscle tissues and the results indicated Hg and Pb were introduced from point and non-point sources, therefore it is of concern. Interspatial comparison with the findings of previous local and international studies showed both species of freshwater eels accumulated Hg to high levels, exceeding the safe limits stipulated in the Malaysian Food Act of 1984, Food Regulations (1985) and USEPA (1997). However, the Target Hazard Quotient (THQ) and Hazard Index (HI) indicated that both freshwater eels from the studied sites are safe to consume as there is no risk posed from consumption based on the health risk assessment results as Pb, Cd and Hg concentrations were under the permissible limits of nutrient intake.